PEMBERDAYAAN MASYARAKAT PETANI KELAPA DENGAN PENERAPAN PENGOLAHAN KELAPA ZERO WASTE DI KECAMATAN OBA KOTA TIDORE KEPULAUAN - Basuki, Natal; Djumadil, Nurdiyanawati; Mahmud, Haris; Sangadji, Suwandi S. (STKIP Persada Khatulistiwa Sintang, 2023)
ABSTRACTThe potential for coconut cultivation produced by the people of Oba District only uses coconut meat as copra so that apart frim the coconut meat, it only becomes waste such as coconut husks, shells and dregs. Apart from that, the potential for coconut cultivation may not necessarily improve the welfare of farmers in Oba District, Tidore Islands City, because copra prices experience fluctuations which ultimately cause losses for coconut export producers. This service program aims to find out some of the problems that exist among farmer partners in Oba District, Tidore Island City in dealing with waste from copra. This is expected to influemce the comfort of life for the surrounding community by reducing pollution and utilizing waste thereby increasing added value to the coconut agro-industry system in Oba District.Keywords: Copra; Environment; Coconut. Zero Waste and WasteABSTRAKPotensi budidaya kelapa yang dihasilkan oleh masyarakat Kecamatan Oba Hanya memanfaatkan daging kelapa sebagai kopra sehingga selain daging kelapanya hanya menjadi limbah seperti sabut kelapa, tempurung dan ampasnya saja. Selain itu, potensi budidaya kelapa belum tentu dapat meningkatkan kesejahteraan petani di Kecamatan Oba, Kota Tidore Kepulauan, karena harga kopra mengalami fluktuasi yang pada akhirnya menyebabkan kerugian bagi produsen ekspor kelapa. Program pengabdian ini bermaksud agar bisa menemukan beberapa persoalan yang ada di mitra petani Kecamatan Oba Kota Tidore Kepulauan dalam menanggulangi limbah dari kopra. Hal ini diharapkan dapat mempengaruhi kenyamanan hidup masyarakat sekitar dengan mengurangi polusi dan memanfaatkan limbah sehingga meningkatkan nilai tambah pada sistem agroindustri kelapa di distrik Oba.Kata Kunci: Kopra; Lingkungan, Kelapa, Zero Waste dan Limbah